Adaptive temperature limits for air-conditioned museums in temperate climates. Issue 6 (18th August 2018) - Kramer, Rick; Schellen, Lisje; Schellen, Henk
ABSTRACT: Indoor temperature ( T ) and relative humidity (RH) are important for collection preservation and thermal comfort in museums. In the 20th century, the notion evolved that T and RH need to be stringently controlled, often resulting in excessive energy consumption. However, recent studies have shown that controlled fluctuations are permissible, enabling improved energy efficiency. Consequently, the thermal comfort requirements are increasingly important to determine temperature limits, but knowledge is limited. Therefore, a thermal comfort survey study and indoor measurements were conducted at Hermitage Amsterdam museum in Amsterdam, the Netherlands for one year, including: (1) monitoring of existing conditions ( T = 21°C, RH = 50%); and (2) an intervention in which T is controlled based on an adaptive comfort approach ( T = 19.5–24°C, RH = 50%). The results show that the thermal comfort of the existing conditions is far from optimum; visitors feel too cool in summer and slightly too warm in winter. The adaptive temperature limits were developed to improve thermal comfort significantly without endangering the collection, thereby saving energy. Furthermore, facilitating visitors to adapt their clothing may contribute to enlarging the temperature bandwidth and improve (individual) thermal comfort.